The role of crystal orientation in the dissolution of UO2 thin films. (December 2018) - Rennie, S.; Lawrence Bright, E.; Sutcliffe, J.E.; Darnbrough, J.E.; Burrows, R.; Rawle, J.; Nicklin, C.; Lander, G.H.; Springell, R.
Highlights: Single crystal UO2 thin films have been used to investigate radiolytic dissolution. (1 1 0) UO2 surfaces were shown to corrode more rapidly than (1 1 1). The (1 1 1) surface of UO2 is shown to passivate after initial dissolution. Results show clear orientation dependence of UO2 dissolution. Abstract: Single crystal [0 0 1], [1 1 0], and [1 1 1]-oriented UO2 thin films were utilised to investigate the orientational dependence of radiolytic dissolution. The films were exposed to water in the presence of a synchrotron X-ray source to induce dissolution, with X-ray reflectivity (XRR) used to observe changes in morphology as a function of exposure time. The [0 0 1] and [1 1 0]-oriented films were found to corrode at comparable rates, however, the [1 1 1] film was significantly more corrosion resistant, passivating after the initial 90 s dissolution period. This result shows the orientational dependence of UO2 dissolution, which may have important consequences for theoretical dissolution models.